Physicochemical properties of breadfruit (Artocarpus Altilis) starch from Margarita island, Venezuela - Alicia Mariela Rincón; Fanny C Padilla (Archivos Latinoamericanos de Nutrición)
Artocarpus altilis, seedless variety, is a fruit-producing plant, which is cultivated in Margarita Island, Venezuela and consumed by inhabitants of the region. The purpose of this study was to evaluate the chemical composition and physical characteristics of fresh fruits, as well as chemical physicochemical, morphometric characteristics, viscoamylograph properties, light transmittance, and digestibility in vitro of extracted starch. The starch yield was 18.5 g/100 g (dw). Scanning electron microscopy showed irregular-rounded granules. Values for swelling power, water absorption and solubility were found to be higher than that of corn and amaranth starch. The amylographic study showed 73.3°C as gelatinization temperature, and high stability during heating and cooling cycles. Artocarpus starch could also be categorized in the group of mixed short chain branched/long chain branched glucan starches, this agrees with digestibility results that showed a high degree of digestibility in vitro. These results might be advantageous in medical and food use.